Fun with SPLDV: Multimedia Lectora Inspire Menguatkan Pemahaman Konsep Matematika Siswa - Eka Resti Wulan; Iffatur Rofiqoh; Zulinda Nur Saidah; Diana Puspitasari (JRPM (Jurnal Review Pembelajaran Matematika), 2021)
This study aims to describe the process of developing interactive multimedia learning mathematics Lectora Inspire that satisfies criteria: valid, practical, and effective to reinforce the conceptual understanding of 8th graders of junior high school, especially on Linear Equation System in Two Variables (LESTV) topic. This research uses the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The result of media and content expert validation showed an average score of 84% and 83.5%, respectively, such that it met the valid criteria and without revision. The result of the student questionnaire said that the media was good with scores of 79% and the average point of the test was 86.5 of 100. It showed that the student concept understanding was complete after using the media. The media need to be improved before it was used broader.